High Q-factor controllable phononic modes in hybrid phononic–dielectric structures - Qiang, Bo (2021)
Phonon polariton resonances in the mid-infrared spectral range demonstrate properties superior to noble metal-based plasmonics, owing to smaller dissipative loss and better field confinement. However, a conventional way to excite the localized phonon resonance involves ion etching, which reduces the attainable quality factors (Q-factors) of the resonators. We show that by introducing a deep subwavelength layer of dielectric gratings on a phononic substrate, localized dipolar resonance and higher order modes with high Q-factors 96 and 195, respectively, can be excited. We further demonstrate, via experiments and simulations, that the resonant wavelength and field confinement can be controlled by coupling the localized hybrid mode with propagating surface phonon-polaritons. We also observed for the first time the coupling between a localized dipolar mode and a propagating higher-order surface phonon-polariton mode. The results will be useful in designing on-chip, low-loss, and highly integrated phononic devices in the infrared spectral domain.